GUIDED STEM CELL CARDIOPOIESIS: DISCOVERY AND TRANSLATION - Behfar, Atta (2008)
Over 1,000 patients have participated worldwide in clinical trials exploring the therapeutic value of bone marrow-derived cells in ischemic heart disease. Meta-analysis evaluation of this global effort indicates that adult stem cell therapy is in general safe, but yields a rather modest level of improvement in cardiac function and structural remodeling in the setting of acute myocardial infarction or chronic heart failure. Although promising, the potential of translating adult stem cell-based therapy from bench to bedside has yet to be fully realized. Inter-trial and inter-patient variability contribute to disparity in the regenerative potential of transplanted stem cells with unpredictable efficacy on follow-up. Strategies that mimic the natural embryonic program for uniform recruitment of cardiogenic progenitors from adult sources are currently tested to secure consistent outcome. Guided cardiopoiesis has been implemented with mesenchymal stem cells obtained from the bone marrow of healthy volunteers, using a cocktail of secreted proteins that recapitulate components of the endodermal secretome critical for cardiogenic induction of the embryonic mesoderm. With appropriate validation of this newly derived cardiopoietic phenotype, the next generation of trials should achieve demonstrable benefit across patient populations.